Silicon-carbon negative electrode material, preparation method thereof, negative electrode sheet and lithium ion battery

CN122950429APending Publication Date: 2026-10-20SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611070141.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本申请的主要目的在于提供一种硅碳负极材料及其制备方法、负极片及锂离子电池,以解决现有技术中硅碳负极材料在匀浆过程中产气量大的问题,以及由其制得的硅碳负极片存在界面阻抗高、功率性能差的问题

Benefits of technology

[0024]应用本申请的技术方案,提供了一种硅碳负极材料,该硅碳负极材料由内到外依次包括内核、中间层和外壳,其中,中间层的材料为氟碳材料,其C-F键具有极强的极性和高键能,使氟碳材料具有较低的表面能,采用具有上述特定氟含量的氟碳材料,能够使中间层具有更好的疏水性,将中间层设置在内核的表面,能够形成疏水屏障,阻隔水系浆料中的水分子与硅碳材料内核接触,从而抑制硅与水中的氢氧根离子(OH-)反应,降低氢气的生成量;同时氟碳材料还能够提供电子导电通道,提高硅碳负极材料的导电性。在中间层的外表面设置无机固态电解质外壳,一方面能够提供二次物理屏障,进一步阻隔水分子的渗透,降低硅碳负极材料在匀浆过程中的产气量;另一方面以无机固态电解质作为外壳材料能够构建高效的锂离子传输网络,并与中间层的氟碳材料协同形成电子-离子双快通道,从而有效提高硅碳负极材料的锂离子扩散速率,进而降低由其制得的负极片的界面阻抗,提高其功率性能。同时,在中间层和外壳这一双重包覆层结构的协同作用下,还能够有效缓解硅碳材料内核在电池充放电循环过程中的体积膨胀,提高硅碳负极材料的结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

This application provides a silicon-carbon anode material, its preparation method, an anode sheet, and a lithium-ion battery. The silicon-carbon anode material has a core-shell structure, comprising a core, an intermediate layer, and an outer shell from the inside out. The core material is silicon-carbon; the intermediate layer is fluorocarbon, with a fluorine content of 10–80 wt%; and the outer shell is an inorganic solid electrolyte. The weight ratio of the core to the total weight of the intermediate layer and the outer shell is 100:(2–10). By constructing a double-layer synergistic coating structure of a fluorocarbon intermediate layer and an inorganic solid electrolyte shell, this application reduces the gas generation of the silicon-carbon anode material during the homogenization process, improving the safety and coating performance during anode sheet production. Furthermore, it enhances the conductivity and lithium-ion diffusion rate of the silicon-carbon anode material, improving the electrochemical performance of the anode sheet prepared from it, thereby improving the power performance and cycle performance of the lithium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery technology, and more specifically, to a silicon-carbon anode material and its preparation method, an anode sheet, and a lithium-ion battery. Background Technology

[0002] Silicon-carbon anode materials are considered an ideal choice for high-energy-density anode materials due to their advantages such as high specific capacity, good safety performance, wide availability of raw materials, and low cost. However, in actual aqueous slurry preparation processes, the elemental silicon remaining on the surface of the silicon-carbon anode material readily reacts with hydroxide ions (OH-) in water. - A violent reaction occurs, producing a large amount of hydrogen gas. Severe gas production can lead to a decrease in the stability of the negative electrode slurry, affecting its coating performance. During the coating process, gas escape can easily form structural defects such as pinholes and cracks, which can easily cause an increase in the internal resistance of the electrode and a deterioration in cycle performance. At the same time, the accumulation of a large amount of hydrogen gas poses an explosion risk, resulting in high safety hazards and restricting the large-scale production of silicon-carbon negative electrode sheets.

[0003] To alleviate the aforementioned problems, the industry currently widely employs chemical vapor deposition (CVD) to construct a carbon coating layer on the surface of silicon-carbon materials. This reduces the direct contact between floating silicon and water on the silicon-carbon surface through physical barriers, thereby suppressing gas generation. However, to avoid high-temperature damage to the carbon matrix structure, CVD processes are typically performed at low temperatures (<600°C). This results in insufficient density of the carbon layer, the presence of micropores, cracks, and uneven coverage, failing to completely block water molecule penetration, and residual gas generation remains significant. Furthermore, simple carbon coating lacks lithium-ion conductivity, offering limited improvement to the electrochemical kinetics of silicon-carbon materials (such as lithium-ion diffusion rate and interfacial impedance), making it difficult to simultaneously achieve high stability and high power performance.

[0004] Therefore, there is an urgent need to develop a silicon-carbon anode material and its preparation method, aiming to effectively reduce the gas production of silicon-carbon anode material during the homogenization process and improve the power performance and lithium-ion transport efficiency of silicon-carbon anode sheets without changing the existing aqueous slurry preparation process. Summary of the Invention

[0005] The main objective of this application is to provide a silicon-carbon anode material and its preparation method, anode sheet and lithium-ion battery, so as to solve the problem of large gas generation during the homogenization process of silicon-carbon anode material in the prior art, and the problems of high interface impedance and poor power performance of silicon-carbon anode sheet made therefrom.

[0006] To achieve the above objectives, this application provides a silicon-carbon anode material having a core-shell structure, comprising a core, an intermediate layer, and an outer shell from the inside out; the core is made of silicon-carbon material; the intermediate layer is made of fluorocarbon material, wherein the fluorine content in the fluorocarbon material is 10-80 wt%; the outer shell is made of inorganic solid electrolyte; and the weight ratio of the core to the total weight of the intermediate layer and the outer shell is 100:(2-10).

[0007] Furthermore, in the silicon-carbon anode material, the weight ratio of the core, intermediate layer and outer shell is 100:(1-5):(1-5).

[0008] Furthermore, the kernel's D 50 It is 4–10 μm.

[0009] Furthermore, the thickness of the intermediate layer is 5–20 nm.

[0010] Furthermore, the thickness of the outer shell is 3–10 nm.

[0011] Furthermore, the inorganic solid electrolyte is selected from one or more of the group consisting of lithium titanium aluminum phosphate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide.

[0012] To achieve the above objectives, another aspect of this application provides a method for preparing the silicon-carbon anode material provided in this application. The method includes: step S1, providing a core, the core being made of silicon-carbon material; and performing vapor deposition coating on the core in a coating gas atmosphere to obtain a precursor; the coating gas includes a fluorine-containing organic compound gas; and step S2, immersing the precursor in an inorganic solid electrolyte solution, and sequentially subjecting it to heat treatment deposition and drying to obtain the silicon-carbon anode material.

[0013] Furthermore, in step S1, the ratio of the volume of the encapsulated gas to the weight of the silicon-carbon material is (400~1000) L:1kg.

[0014] Furthermore, the fluorinated organic compound gas is selected from one or more of the group consisting of tetrafluoromethane, Freon, polyvinylidene fluoride, perfluoropolyether, tetrafluoroethylene, trifluorochloroethylene, perfluorocyclobutane, and fluoroethylene carbonate.

[0015] Furthermore, the coating gas also includes gaseous hydrocarbon compounds; preferably, the weight ratio of the fluorinated organic compound gas to the gaseous hydrocarbon compound in the coating gas is (1-2):(1-2); preferably, the gaseous hydrocarbon compound is selected from one or more of the group consisting of methane, acetylene and propane.

[0016] Furthermore, in step S1, the temperature for vapor deposition coating is 500–580°C, and the time is 12–48 h.

[0017] Furthermore, step S1 also includes a heat preservation treatment performed after the vapor deposition coating is completed; preferably, the temperature of the heat preservation treatment is 500-580°C and the time is 1-2 hours; more preferably, the temperature of the heat preservation treatment is the same as the temperature of the vapor deposition coating.

[0018] Further, in step S2, the inorganic solid electrolyte solution includes an inorganic solid electrolyte and an organic solvent; the weight ratio of the precursor to the inorganic solid electrolyte is 100:(1-7).

[0019] Furthermore, the organic solvent is selected from one or more of the group consisting of N-methylpyrrolidone, acetonitrile, and methanol.

[0020] Furthermore, in step S2, the temperature for heat treatment deposition is 100–200°C, and the time is 2–24 hours.

[0021] Furthermore, the drying temperature is 50–90°C, and the time is 2–12 hours.

[0022] Another aspect of this application provides a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes the silicon-carbon negative electrode material provided in this application.

[0023] A fourth aspect of this application also provides a lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the negative electrode is the aforementioned negative electrode provided in this application.

[0024] Applying the technical solution of this application, a silicon-carbon anode material is provided. This silicon-carbon anode material comprises, from the inside out, a core, an intermediate layer, and a shell. The intermediate layer is made of fluorocarbon material, whose CF bonds have extremely strong polarity and high bond energy, giving the fluorocarbon material a low surface energy. Using a fluorocarbon material with the aforementioned specific fluorine content allows the intermediate layer to have better hydrophobicity. Placing the intermediate layer on the surface of the core forms a hydrophobic barrier, preventing water molecules in the aqueous slurry from contacting the silicon-carbon material core, thereby inhibiting the reaction of silicon with hydroxide ions (OH-) in water. -The reaction reduces hydrogen production; simultaneously, fluorocarbon materials provide electronic conductivity channels, improving the conductivity of silicon-carbon anode materials. An inorganic solid electrolyte shell is placed on the outer surface of the intermediate layer. This provides a secondary physical barrier, further blocking water molecule penetration and reducing gas production during the homogenization process of the silicon-carbon anode material. Furthermore, using the inorganic solid electrolyte as the shell material constructs a highly efficient lithium-ion transport network, which, in conjunction with the fluorocarbon material in the intermediate layer, forms a dual fast electron-ion channel. This effectively increases the lithium-ion diffusion rate of the silicon-carbon anode material, thereby reducing the interfacial impedance of the resulting anode sheet and improving its power performance. Simultaneously, the synergistic effect of this double-layer structure of the intermediate layer and shell effectively mitigates the volume expansion of the silicon-carbon core during battery charge-discharge cycles, improving the structural stability of the silicon-carbon anode material.

[0025] In summary, this application constructs a dual-layer synergistic coating structure consisting of a fluorocarbon intermediate layer and an inorganic solid electrolyte shell. This structure effectively reduces gas generation during the homogenization process of the silicon-carbon anode material, improving safety and coating performance during anode sheet production. Furthermore, it enhances the conductivity and lithium-ion diffusion rate of the silicon-carbon anode material, thereby improving the electrochemical performance of the resulting anode sheet. Applying the silicon-carbon anode material provided in this application to lithium-ion batteries can effectively improve their power performance and cycle stability. Attached Figure Description

[0026] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:

[0027] Figure 1 The SEM image of the silicon-carbon anode material prepared in Example 1 of this application is shown. Detailed Implementation

[0028] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present application will now be described in detail with reference to the embodiments.

[0029] As described in the background art, existing silicon-carbon anode materials suffer from high gas production during the homogenization process, and the silicon-carbon anode sheets produced from them exhibit high interfacial impedance and poor power performance. To address these technical problems, this application provides a silicon-carbon anode material with a core-shell structure, comprising, from the inside out, a core, an intermediate layer, and an outer shell; the core is made of silicon-carbon material; the intermediate layer is made of fluorocarbon material, with a fluorine content of 10–80 wt%; the outer shell is made of inorganic solid electrolyte; and the weight ratio of the core to the total weight of the intermediate layer and the outer shell is 100:(2–10).

[0030] The silicon-carbon anode material provided in this application comprises, from the inside out, a core, an intermediate layer, and a shell. The intermediate layer is made of fluorocarbon material, whose CF bonds possess extremely strong polarity and high bond energy, resulting in a low surface energy. Using a fluorocarbon material with the specific fluorine content described above enhances the hydrophobicity of the intermediate layer. Placing the intermediate layer on the surface of the core forms a hydrophobic barrier, preventing water molecules in the aqueous slurry from contacting the silicon-carbon material core, thereby inhibiting the reaction of silicon with hydroxide ions (OH-) in water. - The reaction reduces hydrogen production; simultaneously, fluorocarbon materials provide electronic conductivity channels, improving the conductivity of silicon-carbon anode materials. An inorganic solid electrolyte shell is placed on the outer surface of the intermediate layer. This provides a secondary physical barrier, further blocking water molecule penetration and reducing gas production during the homogenization process of the silicon-carbon anode material. Furthermore, using the inorganic solid electrolyte as the shell material constructs a highly efficient lithium-ion transport network, which, in conjunction with the fluorocarbon material in the intermediate layer, forms a dual fast electron-ion channel. This effectively increases the lithium-ion diffusion rate of the silicon-carbon anode material, thereby reducing the interfacial impedance of the resulting anode sheet and improving its power performance. Simultaneously, the synergistic effect of this double-layer structure of the intermediate layer and shell effectively mitigates the volume expansion of the silicon-carbon core during battery charge-discharge cycles, improving the structural stability of the silicon-carbon anode material.

[0031] It should be noted that in the aqueous slurry preparation process of the silicon-carbon anode material provided in this application, the reaction equation between water and silicon in the slurry is: Si + 4H2O → H4SiO4 + 2H2 (g).

[0032] The silicon-carbon material used in this application may be of a type commonly used in the art.

[0033] In this application, fluorocarbon materials refer to compounds containing CF bonds. Compared to other ranges, limiting the fluorine content in fluorocarbon materials to the aforementioned specific range can form a denser hydrophobic interlayer with lower surface energy, thereby effectively preventing water molecules in the aqueous slurry from contacting the silicon-carbon material core, further reducing the gas generation of the silicon-carbon anode material during the homogenization process, and also helping to further improve the conductivity of the silicon-carbon anode material.

[0034] Compared to other ranges, limiting the ratio of the core weight to the total weight of the intermediate layer and shell within the aforementioned specific range ensures that the intermediate layer and shell completely and continuously encapsulate the core, thereby effectively preventing water molecules in the aqueous slurry from contacting the silicon-carbon material core and inhibiting the reaction of silicon with OH groups in water. - The reaction reduces the amount of hydrogen generated, while also improving the conductivity and lithium-ion diffusion rate of the silicon-carbon anode material, alleviating the volume expansion of the core during charging and discharging, thereby effectively reducing the interface impedance of the anode sheet made from it and improving its cycle performance and power performance.

[0035] In summary, this application constructs a dual-layer synergistic coating structure consisting of a fluorocarbon intermediate layer and an inorganic solid electrolyte shell. This structure effectively reduces gas generation during the homogenization process of the silicon-carbon anode material, improving safety and coating performance during anode sheet production. Furthermore, it enhances the conductivity and lithium-ion diffusion rate of the silicon-carbon anode material, thereby improving the electrochemical performance of the resulting anode sheet. Applying the silicon-carbon anode material provided in this application to lithium-ion batteries can effectively improve their power performance and cycle stability.

[0036] In a preferred embodiment, the weight ratio of the core, intermediate layer, and outer shell in the silicon-carbon anode material is 100:(1-5):(1-5). Compared to other ranges, limiting the weight ratio of the core, intermediate layer, and outer shell to the above range is beneficial in two ways: firstly, it allows the intermediate layer and outer shell to more completely and continuously coat the core, further preventing water molecules in the aqueous slurry from contacting the silicon-carbon material core, thereby reducing the gas generation of the silicon-carbon anode material during the homogenization process; secondly, it also helps to improve the synergistic effect between the intermediate layer and the outer shell, thereby improving the conductivity and lithium-ion diffusion rate of the silicon-carbon anode material, and further reducing the interfacial impedance of the anode sheet made from it, improving its cycle performance and power performance.

[0037] In a preferred embodiment, the kernel's D 50 The size is 4–10 μm. The kernel's D... 50Including but not limited to the above-mentioned scope, limiting it to the above-mentioned scope is beneficial to improving the dispersibility and coating uniformity of silicon-carbon anode materials during the homogenization and coating process. It is also beneficial to increase the specific surface area of ​​silicon-carbon anode materials and increase the lithium-ion diffusion rate, thereby improving the power performance and cycle stability of lithium-ion batteries made therefrom.

[0038] In order to further prevent water molecules in the aqueous slurry from contacting the silicon-carbon material core, further reduce the gas production of the silicon-carbon anode material during the homogenization process, and further improve the conductivity of the silicon-carbon anode material, in a preferred embodiment, the thickness of the intermediate layer is 5-20 nm.

[0039] In a preferred embodiment, the thickness of the outer shell is 3–10 nm. The thickness of the outer shell includes, but is not limited to, the above range. Limiting it to the above range is beneficial in two ways: firstly, it helps to further reduce the gas generation of the silicon-carbon anode material during the homogenization process; secondly, it helps to increase the lithium-ion diffusion rate of the silicon-carbon anode material, reduce the interface impedance of the anode sheet made therefrom, and improve power performance.

[0040] To further improve the lithium-ion diffusion rate of silicon-carbon anode materials, further reduce the interfacial impedance of the anode sheets made therefrom, and improve power performance, in a preferred embodiment, the inorganic solid electrolyte includes, but is not limited to, one or more of the group consisting of lithium titanium aluminum phosphate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide. Specifically, the inorganic solid electrolyte can be one or more of LATP inorganic solid electrolyte, LLZTO inorganic solid electrolyte, and LLZO inorganic solid electrolyte.

[0041] The second aspect of this application also provides a method for preparing the silicon-carbon anode material provided in this application. The method includes: step S1, providing a core, the core material being silicon-carbon material; and performing vapor deposition coating on the core in a coating gas atmosphere to obtain a precursor; wherein the coating gas includes a fluorine-containing organic compound gas; and step S2, immersing the precursor in an inorganic solid electrolyte solution, and sequentially performing heat treatment deposition and drying to obtain the silicon-carbon anode material.

[0042] In step S1 of the above preparation method, the silicon-carbon material core is coated by vapor deposition in a coating gas atmosphere containing fluorinated organic compounds, allowing the coating gas to deposit on the surface of the silicon-carbon material core to form a fluorocarbon intermediate layer, thus obtaining the precursor. In step S2, the precursor is immersed in an inorganic solid electrolyte solution, and the inorganic solid electrolyte is deposited on the surface of the precursor through heat treatment, forming an inorganic solid electrolyte shell in situ, further improving the surface defects of the precursor, thereby constructing a complete and continuous double-layer coating on the surface of the silicon-carbon material core, thus obtaining a silicon-carbon anode material.

[0043] The silicon-carbon anode material prepared by the above-mentioned preparation method provided in this application includes a core, an intermediate layer, and a shell. The intermediate layer is a fluorocarbon material formed during the vapor deposition coating process of fluorinated organic compound gas. Due to the extremely strong polarity and high bond energy of the CF bond, the fluorocarbon material has a low surface energy, thus enabling the intermediate layer to have better hydrophobicity. Placing the intermediate layer on the surface of the core forms a hydrophobic barrier, preventing water molecules in the aqueous slurry from contacting the silicon-carbon material core and inhibiting the reaction of silicon with hydroxide ions (OH-) in water. - The reaction reduces hydrogen production; simultaneously, fluorocarbon materials provide electronic conductivity channels, improving the conductivity of the resulting silicon-carbon anode material. The inorganic solid electrolyte shell, formed through thermal deposition, provides a secondary physical barrier, further blocking water molecule penetration and reducing gas production during the homogenization process of the silicon-carbon anode material. Furthermore, the inorganic solid electrolyte shell constructs a highly efficient lithium-ion transport network, synergistically forming an electron-ion dual fast channel with the fluorocarbon material in the intermediate layer. This effectively improves the lithium-ion diffusion rate of the resulting silicon-carbon anode material, reduces the interfacial impedance of the anode sheet, and enhances its power performance. Simultaneously, the synergistic effect of this dual-coating structure of the intermediate layer and the shell effectively mitigates the volume expansion of the silicon-carbon core during battery charge-discharge cycles, improving the structural stability of the silicon-carbon anode material.

[0044] In summary, the silicon-carbon anode material prepared by the method described in this application can not only effectively reduce the gas generation during the homogenization process and improve the safety and coating performance of the anode sheet production process, but also improve the conductivity and lithium-ion diffusion rate of the silicon-carbon anode material, thereby enhancing the electrochemical performance of the anode sheet made from it. Applying the prepared silicon-carbon anode material to lithium-ion batteries can effectively improve the power performance and cycle stability of lithium-ion batteries.

[0045] In a preferred embodiment, the ratio of the volume of the encapsulated gas introduced to the weight of the silicon-carbon material is (400-1000) L:1 kg. This ratio includes, but is not limited to, the range described above. Limiting it to this range facilitates the formation of a dense, continuous, and appropriately thick intermediate layer, thereby reducing the gas generation during the homogenization process of the prepared silicon-carbon anode material and also improving the conductivity of the silicon-carbon anode material.

[0046] To promote the formation of a more uniform and dense intermediate layer, in a preferred embodiment, the fluorinated organic compound gas includes, but is not limited to, one or more of the group consisting of tetrafluoromethane, Freon, polyvinylidene fluoride, perfluoropolyether, tetrafluoroethylene, trifluorochloroethylene, perfluorocyclobutane, and fluoroethylene carbonate.

[0047] In a preferred embodiment, the coating gas further includes gaseous hydrocarbon compounds. The introduction of gaseous hydrocarbon compounds is beneficial for increasing the carbon content of the interlayer, enhancing the continuity and density of the interlayer, and also improving the conductivity of the resulting silicon-carbon anode material.

[0048] In a preferred embodiment, the weight ratio of fluorinated organic compound gas to gaseous hydrocarbon compound in the coating gas is (1-2):(1-2). The weight ratio of fluorinated organic compound gas to gaseous hydrocarbon compound includes, but is not limited to, the above range. Limiting it to this range is beneficial for forming a denser and more stable intermediate layer. On the one hand, it helps to prevent water molecules in the aqueous slurry from contacting the silicon-carbon material core, further reducing the gas production of the silicon-carbon anode material during the homogenization process. On the other hand, it helps to improve the conductivity of the silicon-carbon anode material.

[0049] To promote the formation of a denser and more continuous intermediate layer and further improve the conductivity of the silicon-carbon anode material, in a preferred embodiment, the gaseous hydrocarbon compound includes, but is not limited to, one or more of the group consisting of methane, acetylene and propane.

[0050] In a preferred embodiment, in step S1, the temperature for vapor deposition coating is 500–580°C, and the time is 12–48 hours. The temperature and time for vapor deposition coating include, but are not limited to, the above ranges. Limiting them to these ranges is beneficial for improving the efficiency and effectiveness of vapor deposition coating, for forming a more uniform and continuous intermediate layer, thereby reducing the amount of gas generated by the silicon-carbon anode material during the homogenization process, and improving the conductivity of the silicon-carbon anode material.

[0051] To further improve the coating effect of vapor deposition and promote the formation of a more uniform and continuous intermediate layer, in a preferred embodiment, step S1 further includes a heat preservation treatment performed after the vapor deposition coating is completed.

[0052] In a preferred embodiment, the heat preservation treatment is carried out at a temperature of 500–580°C for 1–2 hours. The temperature and time of the heat preservation treatment include, but are not limited to, the above-mentioned ranges. Limiting them to the above-mentioned ranges is beneficial to promoting the formation of a more uniform and continuous intermediate layer.

[0053] To further improve the coating effect of vapor deposition and promote the formation of a more uniform and continuous intermediate layer, preferably, the temperature of the heat preservation treatment is the same as the temperature of vapor deposition.

[0054] In a preferred embodiment, in step S2, the inorganic solid electrolyte solution comprises an inorganic solid electrolyte and an organic solvent, and the weight ratio of the precursor to the inorganic solid electrolyte is 100:(1-7). The weight ratio of the precursor to the inorganic solid electrolyte includes, but is not limited to, the range described above. Limiting it to this range promotes the formation of a continuous and dense inorganic solid electrolyte shell, thereby reducing the gas generation of the silicon-carbon anode material during the homogenization process, increasing the lithium-ion diffusion rate of the obtained silicon-carbon anode material, reducing the interfacial impedance of the anode sheet obtained therefrom, and improving power performance.

[0055] In order to promote the formation of a more uniform and dense inorganic solid electrolyte shell, thereby further improving the lithium-ion diffusion rate of the prepared silicon-carbon anode material, reducing the interface impedance of the anode sheet made therefrom, and improving power performance, in a preferred embodiment, the inorganic solid electrolyte includes, but is not limited to, one or more of the group consisting of lithium titanium aluminum phosphate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide.

[0056] To further improve the dispersibility of the precursor and the inorganic solid electrolyte, thereby further improving the coating effect of subsequent heat treatment deposition, in a preferred embodiment, the organic solvent includes, but is not limited to, one or more of the group consisting of N-methylpyrrolidone, acetonitrile, and methanol.

[0057] In a preferred embodiment, in step S2, the heat treatment deposition temperature is 100–200°C, and the time is 2–24 hours. The heat treatment deposition temperature and time include, but are not limited to, the above ranges. Limiting them within these ranges promotes the formation of a more uniform, dense, and continuous inorganic solid electrolyte shell, thereby reducing the gas generation of the silicon-carbon anode material during the homogenization process. It also helps to increase the lithium-ion diffusion rate of the silicon-carbon anode material, reduce the interfacial impedance of the anode sheet made from it, and improve power performance.

[0058] In order to remove residual organic solvents and further improve the purity of the prepared silicon-carbon anode material, in a preferred embodiment, the drying temperature is 50-90°C and the drying time is 2-12 hours.

[0059] A third aspect of this application also provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the silicon-carbon negative electrode material provided in this application. By constructing a double-layer synergistic coating structure of a fluorocarbon intermediate layer and an inorganic solid electrolyte shell, this application can effectively reduce the gas generation of the silicon-carbon negative electrode material during the homogenization process, improving the safety and coating performance of the negative electrode sheet production process. Furthermore, it can improve the conductivity and lithium-ion diffusion rate of the silicon-carbon negative electrode material, thereby improving the electrochemical performance of the negative electrode sheet made therefrom. Applying the negative electrode sheet made from the silicon-carbon negative electrode material provided in this application to lithium-ion batteries can effectively improve the power performance and cycle stability of lithium-ion batteries.

[0060] A fourth aspect of this application also provides a lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive and negative electrode, wherein the negative electrode is the aforementioned negative electrode provided in this application. The aforementioned negative electrode provided in this application includes the aforementioned silicon-carbon negative electrode material. This silicon-carbon negative electrode material, by constructing a double-layer synergistic coating structure of a fluorocarbon intermediate layer and an inorganic solid electrolyte shell, can effectively reduce the gas generation of the silicon-carbon negative electrode material during the homogenization process, improve the safety and coating performance during the production process of the negative electrode, and the negative electrode obtained therefrom has low interfacial resistance, excellent power performance, and cycle performance. Its application in lithium-ion batteries can effectively improve the power performance and cycle stability of lithium-ion batteries.

[0061] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0062] Example 1

[0063] A method for preparing a silicon-carbon anode material specifically includes the following steps:

[0064] (1) 1000g of vapor-deposited silicon-carbon anode material (D 50 The precursor (8μm thick, Lanxi Zhide New Energy Materials Co., Ltd., S0310a) was placed in a rotary kiln, and 600L of coating gas, including tetrafluoromethane and acetylene (weight ratio 1:2), was introduced at a flow rate of 0.5L / min. The rotary kiln speed was set to 60r / min and the temperature to 580℃. Then, vapor deposition coating was performed at this temperature for 24h. After completion, the rotary kiln speed and temperature were maintained, and the temperature was kept for another 1h to obtain the precursor. The precursor consisted of a silicon-carbon material core and an 8nm thick fluorocarbon intermediate layer covering its surface, with a weight ratio of fluorocarbon intermediate layer to silicon-carbon material of 2:100.

[0065] (2) In a closed reactor, add 1000g of the precursor obtained in step (1), 20g of LLZTO inorganic solid electrolyte and 20L of N-methylpyrrolidone (NMP), mix evenly, and heat-treat at 150°C for 12h to deposit the inorganic solid electrolyte on the surface of the precursor to form an inorganic solid electrolyte shell; after completion, dry at 80°C for 5h to obtain silicon-carbon anode material.

[0066] The silicon-carbon anode material prepared in Example 1 has a core-shell structure, which consists of a silicon-carbon core, an 8nm thick fluorocarbon intermediate layer, and a 4nm thick inorganic solid electrolyte shell from the inside out; wherein, the weight ratio of the core, intermediate layer and shell is 100:2:2; in the intermediate layer, the content of fluorine is 50wt% and the content of carbon is 50wt%.

[0067] The SEM image of the silicon-carbon anode material prepared in Example 1 is shown below. Figure 1 As shown, by Figure 1 It can be seen that the silicon-carbon anode material prepared in Example 1 is granular with a particle size between 5 and 10 μm.

[0068] Example 2

[0069] The difference from Example 1 is that in step (1), the amount of gas introduced and the temperature and time of vapor deposition are adjusted so that the weight ratio of the fluorocarbon intermediate layer to the silicon carbon material is 1:100; at the same time, in step (2), the amount of inorganic solid electrolyte is adjusted to 10g so that the weight ratio of the core, intermediate layer and shell of the silicon carbon anode material is 100:1:1; the remaining steps are the same as in Example 1.

[0070] Example 3

[0071] The difference from Example 1 is that in step (1), the amount of gas introduced and the temperature and time of vapor deposition are adjusted so that the weight ratio of the fluorocarbon intermediate layer to the silicon-carbon material is 4:100; at the same time, in step (2), the amount of inorganic solid electrolyte is adjusted to 40g so that the weight ratio of the core, intermediate layer and shell of the silicon-carbon anode material is 100:4:4; the remaining steps are the same as in Example 1.

[0072] Example 4

[0073] The difference from Example 1 is that in step (1), the amount of gas introduced and the temperature and time of vapor deposition are adjusted so that the weight ratio of the fluorocarbon intermediate layer to the silicon-carbon material is 6:100; at the same time, in step (2), the amount of inorganic solid electrolyte is adjusted to 60g so that the weight ratio of the core, intermediate layer and shell of the silicon-carbon anode material is 100:6:6; the remaining steps are the same as in Example 1.

[0074] Example 5

[0075] The difference from Example 1 is that: in step (1), the amount of gas introduced is adjusted so that the thickness of the intermediate layer of the silicon-carbon anode material is 5nm; in step (2), the amount of inorganic solid electrolyte is adjusted so that the thickness of the outer shell of the silicon-carbon anode material is 3nm; the remaining steps are the same as in Example 1.

[0076] Example 6

[0077] The difference from Example 1 is that: in step (1), the amount of gas introduced is adjusted so that the thickness of the intermediate layer of the silicon-carbon anode material is 20 nm; in step (2), the amount of inorganic solid electrolyte is adjusted so that the thickness of the outer shell of the silicon-carbon anode material is 10 nm; the remaining steps are the same as in Example 1.

[0078] Example 7

[0079] The difference from Example 1 is that in step (1), the amount of gas introduced is adjusted so that the thickness of the intermediate layer of the silicon-carbon anode material is 1 nm; the remaining steps are the same as in Example 1.

[0080] Example 8

[0081] The difference from Example 1 is that in step (2), the amount of inorganic solid electrolyte is adjusted so that the thickness of the shell of the silicon-carbon anode material is 1 nm; the remaining steps are the same as in Example 1.

[0082] Example 9

[0083] The difference from Example 1 is that in step (1), the content of tetrafluoromethane in the coating gas is adjusted so that the content of fluorine in the intermediate layer of the silicon-carbon anode material is 10wt%; the remaining steps are the same as in Example 1.

[0084] Example 10

[0085] The difference from Example 1 is that in step (1), the content of tetrafluoromethane in the coating gas is adjusted so that the content of fluorine in the intermediate layer of the silicon-carbon anode material is 80wt%; the remaining steps are the same as in Example 1.

[0086] Example 11

[0087] The difference from Example 1 is that: in step (1), no heat preservation treatment was performed, and the precursor was obtained after the vapor deposition coating was completed; the remaining steps are the same as in Example 1.

[0088] Example 12

[0089] The difference from Example 1 is that in step (1), the temperature of vapor deposition coating is adjusted to 550°C and the time is adjusted to 48h; the remaining steps are the same as in Example 1.

[0090] Example 13

[0091] The difference from Example 1 is that in step (1), the temperature of vapor deposition coating is adjusted to 500°C and the time is adjusted to 12h; the remaining steps are the same as in Example 1.

[0092] Example 14

[0093] The difference from Example 1 is that in step (1), the temperature of vapor deposition coating is adjusted to 400°C; the remaining steps are the same as in Example 1.

[0094] Example 15

[0095] The difference from Example 1 is that in step (1), the temperature of vapor deposition coating is adjusted to 800°C; the remaining steps are the same as in Example 1.

[0096] The weight ratio of the core, intermediate layer and outer shell, the thickness of the intermediate layer and outer shell, and the fluorine content in the intermediate layer of the silicon-carbon anode materials prepared in Examples 1 to 15 of this application are shown in Table 1.

[0097] Table 1

[0098]

[0099] Comparative Example 1

[0100] The difference from Example 1 is that step (2) is omitted, and the precursor obtained in step (1) is used as the silicon-carbon anode material; the remaining steps are the same as in Example 1.

[0101] The silicon-carbon anode material prepared in Comparative Example 1 includes a silicon-carbon material core and a fluorinated carbon coating layer covering its surface, without introducing an inorganic solid electrolyte shell; wherein, the weight ratio of the silicon-carbon material core to the fluorinated carbon coating layer is 100:2, the thickness of the fluorinated carbon coating layer is 8 nm, and its fluorine content is 50 wt%.

[0102] Comparative Example 2

[0103] A method for preparing a silicon-carbon anode material includes the following steps: In a closed reaction vessel, 1000g of silicon-carbon material (from the same source as in Example 1), 20g of LLZTO inorganic solid electrolyte and 20L of N-methylpyrrolidone (NMP) are added and mixed evenly. The mixture is then heat-treated at 150°C for 12h to deposit the inorganic solid electrolyte on the surface of the silicon-carbon material, forming an inorganic solid electrolyte coating layer. After completion, the mixture is dried at 80°C for 5h to obtain the silicon-carbon anode material.

[0104] The silicon-carbon anode material prepared in Comparative Example 2 includes a silicon-carbon material core and an inorganic solid electrolyte coating layer covering its surface, without introducing a fluorocarbon intermediate layer; wherein, the weight ratio of the silicon-carbon material core to the inorganic solid electrolyte coating layer is 100:2, and the thickness of the inorganic solid electrolyte coating layer is 4 nm.

[0105] Comparative Example 3

[0106] A method for preparing a silicon-carbon anode material includes the following steps: placing vapor-deposited silicon-carbon material (from the same source as in Example 1) in a rotary kiln, introducing nitrogen as a protective gas, and setting the nitrogen flow rate to 1 L / min; setting the operating parameters of the rotary kiln to a pressure of 1 atm and a rotation speed of 60 r / min, heating to 750°C at a heating rate of 5°C / min for sintering treatment; when the temperature reaches 750°C, introducing 1500 L of acetylene into the rotary kiln at a rate of 3 L / min, and continuing the sintering treatment for 10 h; after completion, allowing it to cool naturally, and then sieving it in a 300-mesh vibrating sieve (vibration frequency of 3600 times / min) to obtain the silicon-carbon anode material.

[0107] The silicon-carbon anode material prepared in Comparative Example 3 includes a silicon-carbon material core and a carbon coating layer covering its surface, without introducing a fluorocarbon intermediate layer and an inorganic solid electrolyte shell; wherein, the weight ratio of the silicon-carbon material core to the carbon coating layer is 100:2, and the thickness of the carbon coating layer is 5 nm.

[0108] Comparative Example 4

[0109] The difference from Example 1 is that in step (1), the content of tetrafluoromethane in the coating gas is adjusted so that the content of fluorine in the intermediate layer of the silicon-carbon anode material is 5wt%; the remaining steps are the same as in Example 1.

[0110] The gas production of the silicon-carbon anode materials prepared in all the above embodiments and comparative examples of this application was tested. The specific test steps are as follows:

[0111] (1) Preparation of the slurry to be tested: Weigh the negative electrode material, binder (including polyacrylic acid PAA and styrene-butadiene rubber SBR with a weight ratio of 1:1:1:15 to obtain the slurry to be tested; wherein, the negative electrode material is the silicon-carbon negative electrode material prepared in Examples 1 to 15 and Comparative Examples 1 to 8 of this application respectively.

[0112] (2) Weigh 25g of the slurry to be tested and place it in a sealed bag with a single-sided opening (size 9cm×11cm). Then seal the single-sided opening of the sealed bag with a hot-press sealing machine to obtain the sample to be tested. Weigh the sample to be tested using a density measuring instrument ST300A and record the mass data m0.

[0113] (3) Allow the sample to stand in a sealed environment at 25°C. Weigh the sample using a density meter every 24 hours and record the mass data m. i Repeat 3 times, i=1, 2, 3.

[0114] Calculate the gas production rate according to formula (1). (1), where V is the gas production rate; m0 is the initial weight of the sample to be tested; m i The weight of the sample to be tested is i after standing for i×24h, where i=1, 2, 3; The density of water is 1 g / cm³. 3 .

[0115] Table 2 shows the gas production test data of the silicon-carbon anode materials prepared in all the above embodiments and comparative examples of this application.

[0116] Table 2

[0117]

[0118] It should be noted that in Table 2 above, the 24-hour gas production of Examples 1 and 10 is 0. This may be because the difference between the weight of the sample to be tested after 24 hours and the initial weight of the sample to be tested is very small, which is lower than the detection limit of the density measuring instrument, resulting in inaccurate measurement and thus the calculated gas production is 0. This shows that the gas production of the silicon-carbon anode materials prepared in Examples 1 and 10 of this application is indeed very small.

[0119] Application Examples

[0120] The lithium-ion battery was assembled according to the following method: (1) Preparation of positive electrode sheet: The positive electrode active material Ni88, conductive agent and binder polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 98:1:1, and then N-methylpyrrolidone (NMP) was added and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry was coated on the surface of a 12μm thick aluminum foil, and then dried at 80°C for 0.5h to obtain a positive electrode sheet with a thickness of 110μm; (2) Preparation of negative electrode sheet: The silicon-carbon negative electrode material (the silicon-carbon negative electrode material prepared in Examples 1 to 15 and Comparative Examples 1 to 8 of this application, respectively), graphite, conductive agent and binder (including polyacrylic acid PAA and styrene-butadiene rubber SBR in a weight ratio of 1:1) were mixed evenly in a weight ratio of 20:70:2:8, and water was added to obtain a negative electrode slurry. Materials; The negative electrode slurry was coated on the surface of a 6μm thick copper foil and then dried at 80°C for 0.5h to obtain a negative electrode sheet with a thickness of 95μm; (3) Lithium-ion battery assembly: Assembly was carried out in a glove box filled with argon gas, using the positive electrode sheet prepared above as the positive electrode and the negative electrode sheet prepared above as the negative electrode; LiPF6, fluoroethylene carbonate (FEC, content of 10wt% of electrolyte) and a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC to DEC is 1:1) were mixed to prepare a 1mol / L LiPF6 electrolyte; The separator was a polyethylene separator with double-sided ceramic coating (the thickness of the polyethylene substrate is 7μm and the thickness of the single-sided ceramic coating is 1.5μm); The lithium-ion battery was assembled.

[0121] The following performance tests were performed on the lithium-ion batteries assembled in all the above embodiments and comparative examples: (1) Power performance: Using the Xinwei test cabinet, charge and discharge tests were performed at 25°C with 0.33C and 3C rates in the voltage range of 2.5 to 4.25V. The specific capacity of 0.33C discharge and 3C discharge were measured, and the ratio of 3C discharge specific capacity to 0.33C discharge specific capacity was calculated and recorded as power performance, i.e., power performance (%) = 3C discharge specific capacity / 0.33C discharge specific capacity; (2) Capacity retention rate: 600 cycles were performed at 25°C, 0.33C rate, and voltage range of 2.5 to 4.25V, and the capacity retention rate after 600 cycles was recorded.

[0122] The test results are shown in Table 3.

[0123] Table 3

[0124]

[0125] As can be seen from the above description, the embodiments of this application achieve the following technical effects:

[0126] Comparing Example 1 and Comparative Examples 1 to 3, and combining the data in Tables 2 and 3, it can be seen that by introducing specific types of intermediate layers and outer shells, the synergistic effect of the double coating structure can significantly reduce the gas generation of silicon-carbon anode materials during the homogenization process, improve the conductivity and lithium-ion diffusion rate of silicon-carbon anode materials, reduce the interfacial impedance of the anode sheet, effectively alleviate the volume expansion of the silicon-carbon material core during battery charge-discharge cycles, improve the structural stability of silicon-carbon anode materials, and thus significantly improve the power performance and cycle performance of the prepared lithium-ion battery.

[0127] Comparing Examples 1, 9, and 10 with Comparative Example 4, and combining the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the fluorine content in the interlayer material to the above-mentioned specific range can form a denser hydrophobic interlayer with lower surface energy. This effectively blocks water molecules in the aqueous slurry from contacting the silicon-carbon material core, reduces the gas generation of the silicon-carbon anode material during the homogenization process, and improves the conductivity of the silicon-carbon anode material, thereby significantly improving the power performance and cycle performance of the prepared lithium-ion battery.

[0128] Comparing Examples 1 to 4 and Example 6, and considering the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the weight ratio of the core, intermediate layer, and outer shell of the silicon-carbon anode material to the preferred range described above in this application is beneficial for the intermediate layer and outer shell to more completely and continuously coat the core, reducing the gas generation of the silicon-carbon anode material during the homogenization process. It also helps to improve the synergistic effect between the intermediate layer and the outer shell, thereby improving the conductivity and lithium-ion diffusion rate of the silicon-carbon anode material, reducing the interface impedance of the anode sheet, and thus improving the cycle performance and power performance of the prepared lithium-ion battery.

[0129] Comparing Examples 1, 5 to 7, and in conjunction with the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the thickness of the intermediate layer of the silicon-carbon anode material within the preferred range described above in this application is beneficial to reducing the gas production of the silicon-carbon anode material during the homogenization process, improving the conductivity of the silicon-carbon anode material, and also beneficial to improving the power performance and cycle performance of the resulting lithium-ion battery.

[0130] Comparing Examples 1, 5, 6, and 8, and combining the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the thickness of the shell of the silicon-carbon anode material to the preferred range described above in this application is beneficial to reducing the gas production of the silicon-carbon anode material during the homogenization process, and also beneficial to increasing the lithium-ion diffusion rate of the silicon-carbon anode material, reducing the interface impedance of the anode sheet made therefrom, thereby improving the power performance and cycle performance of the resulting lithium-ion battery.

[0131] Comparing Examples 1 and 11, and combining the data in Tables 2 and 3, it can be seen that, compared with other methods, the heat preservation treatment after vapor deposition coating is beneficial to promote the formation of a more uniform and continuous intermediate layer, thereby reducing the gas generation of silicon-carbon anode material during homogenization, improving the conductivity of silicon-carbon anode material, and thus improving the power performance and cycle performance of the prepared lithium-ion battery.

[0132] Comparing Examples 1, 12 to 15, and combining the data in Tables 2 and 3, it can be seen that, compared to other ranges, limiting the temperature and time of vapor deposition coating to the preferred range described above in this application is beneficial to forming a more uniform and continuous intermediate layer, thereby reducing the amount of gas generated by the silicon-carbon anode material during the homogenization process, improving the conductivity of the silicon-carbon anode material, and thus improving the power performance and cycle performance of the prepared lithium-ion battery.

[0133] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in a sequence other than those described herein.

[0134] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A silicon-carbon anode material, characterized in that, The silicon-carbon anode material has a core-shell structure, comprising a core, an intermediate layer, and an outer shell from the inside out; the core is made of silicon-carbon material; the intermediate layer is made of fluorocarbon material, and the fluorine content in the fluorocarbon material is 10-80 wt%; the outer shell is made of inorganic solid electrolyte; the weight ratio of the core to the total weight of the intermediate layer and the outer shell is 100:(2-10).

2. The silicon-carbon anode material according to claim 1, characterized in that, In the silicon-carbon anode material, the weight ratio of the core, the intermediate layer and the outer shell is 100:(1-5):(1-5). Preferably, the kernel's D 50 It is 4–10 μm.

3. The silicon-carbon anode material according to claim 1 or 2, characterized in that, The thickness of the intermediate layer is 5–20 nm.

4. The silicon-carbon anode material according to any one of claims 1 to 3, characterized in that, The thickness of the outer shell is 3–10 nm; Preferably, the inorganic solid electrolyte is selected from one or more of the group consisting of lithium titanium aluminum phosphate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide.

5. A method for preparing a silicon-carbon anode material according to any one of claims 1 to 4, characterized in that, The preparation method includes: Step S1: Provide a core, wherein the core is made of silicon-carbon material; coat the core with vapor phase deposition in a coating gas atmosphere to obtain a precursor; the coating gas includes a fluorine-containing organic compound gas; Step S2: The precursor is immersed in an inorganic solid electrolyte solution, and then subjected to heat treatment deposition and drying to obtain the silicon-carbon anode material.

6. The method for preparing the silicon-carbon anode material according to claim 5, characterized in that, In step S1, the ratio of the volume of the encapsulated gas to the weight of the silicon-carbon material is (400-1000) L:1kg. Preferably, the fluorinated organic compound gas is selected from one or more of the group consisting of tetrafluoromethane, Freon, polyvinylidene fluoride, perfluoropolyether, tetrafluoroethylene, trifluorochloroethylene, perfluorocyclobutane, and fluoroethylene carbonate. Preferably, the coating gas further includes gaseous hydrocarbon compounds; more preferably, the weight ratio of the fluorinated organic compound gas to the gaseous hydrocarbon compound in the coating gas is (1-2):(1-2); even more preferably, the gaseous hydrocarbon compound is selected from one or more of the group consisting of methane, acetylene, and propane.

7. The method for preparing the silicon-carbon anode material according to claim 6, characterized in that, In step S1, the temperature of the vapor deposition coating is 500-580℃ and the time is 12-48h. Preferably, step S1 further includes a heat preservation treatment performed after the vapor deposition coating is completed; Preferably, the temperature of the heat preservation treatment is 500-580°C and the time is 1-2 hours; more preferably, the temperature of the heat preservation treatment is the same as the temperature of the vapor deposition coating.

8. The method for preparing the silicon-carbon anode material according to any one of claims 5 to 7, characterized in that, In step S2, the inorganic solid electrolyte solution includes an inorganic solid electrolyte and an organic solvent; the weight ratio of the precursor to the inorganic solid electrolyte is 100:(1-7). Preferably, the organic solvent is selected from one or more of the group consisting of N-methylpyrrolidone, acetonitrile, and methanol; Preferably, in step S2, the temperature of the heat treatment deposition is 100-200°C, and the time is 2-24 hours; Preferably, the drying temperature is 50–90°C and the drying time is 2–12 hours.

9. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, characterized in that, The negative electrode active material layer comprises the silicon-carbon negative electrode material according to any one of claims 1 to 4.

10. A lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, characterized in that, The negative electrode is the negative electrode as described in claim 9.